Mulching with Terrace Strengthen on Surface Runoff, Erosion, and Sediment Enrichment Ratio - Trinugraheni Trinugraheni; Jaka Suyana; Sumarno Sumarno (Perkumpulan Agroteknologi/Agroekoteknologi Indonesia, 2017)
Land degradation causes increase erosion on agricultural land. Andisol soil contains more fractions sand making aggregate easily dispersed. Soil loss due to erosion can lead to nutrients loss needed by plants. Corn stem mulching to reduce erosion and runoff.Corn stem mulch can be combined with terrace strengthen to decrease surface runoff and erosion.The study used randomized block design with 4 treatments and repeated 3 times as a block so that there are 12 experimental unit. Category of group iscabbage, red lentils and white lentils. The results showed that corn stem mulch 12 ton-1ha with kalanjana + annona able to reduce 4,5% of surface runoff, erosion 15,5%.Corn stem mulch 4 ton-1ha with Vetiverazizanioides+Annona squamosa as terrace strengthen withSER (Sediment Enrichment Ratio) has a (C-organic = 0,94; N-total = 1,04; P-total = 2,21; P-available = 1,40; K-total of 0,87; K-available 0,73) and suppresses loss nutrients in the Andisol soil.